CSM In Motion Vector Steganalysis: The Effect of Coders on Motion Vectors in H.264 Video Encoding - Lachner, Verena; Schaar, Katharina; Zimmermann, Ralf (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2023)
Cover-Source Mismatch (CSM) has long been recognized as a major challenge in machine-learning based image steganalysis. However, little is known about the impact of CSM on motion vector (MV) based video steganalysis. As CSM stemming from factors at the end of the processing pipeline is particularly noticeable, we conduct a study on the impact of H.264 coders on motion vectors. This paper compares the outputs of compression operations of a range of coders according to specific MV statistics. We identify discrepancies between the coders in all cases and point out why this is an indicator for CSM. This result paves the way for more extensive research on CSM in MV steganalysis.